2012
DOI: 10.1073/pnas.1115906109
|View full text |Cite
|
Sign up to set email alerts
|

RNAs in Epstein–Barr virions control early steps of infection

Abstract: Herpesviruses are dsDNA viruses, but their virions may additionally contain RNAs that can be transduced to recipient cells. The biological functions of herpes virion RNA species are unknown. Here we address this issue for EBV, a widespread human herpesvirus with oncogenic potential. We show that EBV-derived particles that include virions, virus-like particles, and subviral vesicles contain viral mRNAs, microRNAs, and other noncoding RNAs. Viral RNAs were transduced during infection and deployed immediate funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
99
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 65 publications
2
99
1
Order By: Relevance
“…The mechanisms of regulation we identified in that context-that is, regulation of MHC II, lysosomal enzymes, and IL-12-are likely relevant in latency as well and may explain why EBNA-specific CD4 + T cells are generally impaired in recognizing LCLs (46). The present study focused on established latency, but because we observed a strong miRNA regulation of EBNA1 recognition by CD8 + T cells already on days 1, 2, and 3 after infection, the hypothesis that EBV miRNAs generally suppress CD8 + T-cell recognition already in the first days of infection during prelatency (13,22,47) deserves closer investigation in the future.…”
Section: Discussionmentioning
confidence: 58%
“…The mechanisms of regulation we identified in that context-that is, regulation of MHC II, lysosomal enzymes, and IL-12-are likely relevant in latency as well and may explain why EBNA-specific CD4 + T cells are generally impaired in recognizing LCLs (46). The present study focused on established latency, but because we observed a strong miRNA regulation of EBNA1 recognition by CD8 + T cells already on days 1, 2, and 3 after infection, the hypothesis that EBV miRNAs generally suppress CD8 + T-cell recognition already in the first days of infection during prelatency (13,22,47) deserves closer investigation in the future.…”
Section: Discussionmentioning
confidence: 58%
“…Indeed, chronic activation of antiviral immunity by erroneous detection of extracellular RNA drives autoimmunity in predisposed individuals (20). Although binding of proinflammatory EBERs to cytoplasmic sensors has been reported in vitro (9)(10)(11)(12), there is little evidence that this may occur in latently infected B cells in a physiologically relevant context (21), but there are multiple indications that EBERs are secreted from infected cells (9,22,23).…”
Section: Significancementioning
confidence: 99%
“…The primary infection of B cells by EBV shows an expression of lytic genes (21)(22)(23). The expression of the lytic genes before the latent genes during early infection suggests that this initial expression of lytic genes is important for the successful establishment of EBV latency (21,22).…”
mentioning
confidence: 99%